Mitochondrial function in skeletal muscle contributes to reproductive endothermy in tegu lizards (Salvator merianae) - Hervas, Livia Saccani [UNESP]; do Amaral-Silva, Lara; Sartori, Marina Rincon; Guadalupe-Silva, Ane [UNESP]; Gargaglioni, Luciane H. [UNESP]; Lerchner, Johannes; Oliveira, Marcos Túlio [UNESP]; Bícego, Kênia Cardoso [UNESP] (Wiley, 2024)
Aim: In cyclic climate variations, including seasonal changes, many animals regulate their energy demands to overcome critical transitory moments, restricting their high-demand activities to phases of resource abundance, enabling rapid growth and reproduction. Tegu lizards (Salvator merianae) are ectotherms with a robust annual cycle, being active during summer, hibernating during winter, and presenting a remarkable endothermy during reproduction in spring. Here, we evaluated whether changes in mitochondrial respiratory physiology in skeletal muscle could serve as a mechanism for the increased thermogenesis observed during the tegu's reproductive endothermy. Methods: We performed high-resolution respirometry and calorimetry in permeabilized red and white muscle fibers, sampled during summer (activity) and spring (high activity and reproduction), in association with citrate synthase measurements. Results: During spring, the muscle fibers exhibited increased oxidative phosphorylation. They also enhanced uncoupled respiration and heat production via adenine nucleotide translocase (ANT), but not via uncoupling proteins (UCP). Citrate synthase activity was higher during the spring, suggesting greater mitochondrial density compared to the summer. These findings were consistent across both sexes and muscle types (red and white). Conclusion: The current results highlight potential cellular thermogenic mechanisms in an ectothermic reptile that contribute to transient endothermy. Our study indicates that the unique feature of transitioning to endothermy through nonshivering thermogenesis during the reproductive phase may be facilitated by higher mitochondrial density, function, and uncoupling within the skeletal muscle. This knowledge contributes significant elements to the broader picture of models for the evolution of endothermy, particularly in relation to the enhancement of aerobic capacity.
Keywords: ant; facultative endothermy; mitochondrial density; reproduction; reptile; thermogenesis